Immunopathogenesis and Susceptibility to Cutaneous Leishmaniasis among Iraqi Patients - Al-Bermani, AbeerSekarnaji; Al-Shibly, IfadKerim; Alyasari, Hadi Fadhil; AlKhafaji, Falih Hasan Mohammad (Annals of the Romanian society for cell biology, 2021)
Abstract Leishmaniasisa parasitic disease that affects humans and animals, is mainly transmitted from one host to another through the bite of an infected phlebotomus sand fly vector.Theaim of this study is to evaluate the mechanism of immune-pathogenesis of leishmaniasis, and to determine a possible role for genetic polymorphism in selected gene on the susceptibility to leishmaniasis among Iraqi patients.The present study enrolled a total of 116 subjects in a case-control study design (58 patients with Cutaneous Leishmaniasis and 58 apparently healthy subjects of serving as a control group) for a period from May 2020 to February 2021,all patients 58 in this study were referred and diagnosed clinically in the dermatology outpatient clinic in the Babylon hospital, Iraq. Median serum level of CAMP LL37 in patients with Cutaneous Leishmaniasis was 8.39 (6.19) pg/ml, while that of control groups was 4.83 (1.04) pg/ml.Hence serum level of CAMP LL37 was significantly higher in patients with Cutaneous Leishmaniasis than control group (P < 0.001).PCR-RFLP for TOLLIP polymorphism Hardy Weinberg equation was applied to node genotypes, CC, CT and TT, distribution within the control group and results are showed the homozygous wild genotype CC was encountered in 37 out of 50 control subjects; the heterozygous CT genotype was seen in 9 out of 50 control subjects and the homozygous mutant TT genotype was seen in 4 out of 50 control subjects, . The disease is endemic in more than 98 countries and an estimated 350 million people are at risk.The 84% of global CL incidence in 2016 were reported in Afghanistan, Algeria, Brazil, Colombia, Iraq, Pakistan, Peru,theSyrian Arab Republic, Tunisia, and Yemen2.Early identification of the infectious nature of the disease is dated back to more than 100 years ago and the pioneer who made that recognition was the Russian physician "Piotr FokichBorovsky" who successfully isolated the parasite from Asian cutaneous lesions3.Cutaneous leishmaniasis is an endemic disease in Iraq, mainly in central and southern regions4.Immunity to leishmaniasis is mainly initiated by way of innate immune cells followed by cell-mediated immune response5.Granule-secreted enzymes (Granzymes) are a family of serine proteases discovered in the mid1980s and proposed to be key mediators of cytotoxic T lymphocyte (CTL) and natural killer (NK) granule exocytosis-mediated cell death.One likely explanation of how cytotoxic cells mediate inflammation and tissue injury in CL is that, after degranulation of cytotoxic cells, granzyme B and perforin are released into the extracellular space, inducing apoptosis of infected macrophages and bystander cells6.Cathelicidins, are key players in the human host's immune defense. Material and Patients Blood samples were taken from all subjects in the study for immunological, genetic and epidemiologic study. 1.Patients:A hundred and sixteen subjects from different ages and both genders were enrolled in this case-control study, this study groups were classified as the following,including58 patients with Cutaneous Leishmaniasis (Baghdad boil) (case group)and 58 normal healthy individuals no CL (control group).All patients in this study were referred from different regions of Iraq and were diagnosed clinically by consultant dermatologist in dermatology out patients clinic of central general hospitals of Al- Hilla,Iraq from September-2020 to February-2021).